2+6g=11+-3g

Simple and best practice solution for 2+6g=11+-3g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+6g=11+-3g equation:



2+6g=11+-3g
We move all terms to the left:
2+6g-(11+-3g)=0
We add all the numbers together, and all the variables
6g-(-3g)+2=0
We get rid of parentheses
6g+3g+2=0
We add all the numbers together, and all the variables
9g+2=0
We move all terms containing g to the left, all other terms to the right
9g=-2
g=-2/9
g=-2/9

See similar equations:

| 1.1/3.3=6.9/w | | (2x)^2-5x+2=(1+3)x^2 | | 5x-8+5x+2+4x+4x+96=540 | | -2(x+-3)+4x=-(-x+1) | | 16=2(1+7a) | | 32+91=5y | | 3x+14=-9x-22 | | 3(1+4x)=87 | | 2x+2x+6+6=6•2x | | 40×3x+x=180 | | 6(8+3x)=-28+18x | | 4y-7y=-8+y | | 42=1/2(x+3)(2x+8) | | 5(2+v)+35v=14V | | 3x-4=1x+4 | | 4|p−3|=|2p+8|4|p−3|=|2p+8|. | | m^2+2m+2=10 | | 8(x-1)=6(x-6) | | 448.98=240+0.86x | | x-(-24)=40 | | 4/8=i/27 | | 5-3(x-7)=-5x-8 | | (X+3)^4+3(x+3)^2=4 | | Y0=m0m | | 1k=1 | | 250+20p=3,756 | | 39+9s=750 | | 3x+2=3(2x+4) | | 9=15w-4(3w-1) | | 6+19y-3=8y+115-5y | | 0.06(4t-7)=0.24(t+4)-1.38 | | 3x+2=6(x+1) |

Equations solver categories